2018
DOI: 10.1080/00220388.2018.1464143
|View full text |Cite
|
Sign up to set email alerts
|

Do Beliefs About Herbicide Quality Correspond with Actual Quality in Local Markets? Evidence from Uganda

Abstract: Adoption of modern agricultural inputs in Africa remains low, restraining agricultural productivity and poverty reduction. Low quality agricultural inputs may in part explain low adoption rates, but only if farmers are aware that some inputs are low quality. We report the results of laboratory tests of the quality of glyphosate herbicide in Uganda and investigate whether farmers' beliefs about the prevalence of counterfeiting and adulteration are consistent with the prevalence of low quality in their local mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 30 publications
3
62
0
Order By: Relevance
“…In the context of frauds, high risk perception enables farmers to protect themselves by purchasing only products duly registered by governmental regulators [36]. This result is in line with the study of Ashour et al (2019) [8], who revealed that 80% of the farmers in Uganda had high beliefs about counterfeit herbicides. On the other hand, a comparison of farmers who had purchased fraudulent pesticides and those who had not showed an interesting result.…”
Section: Plos Onesupporting
confidence: 80%
See 2 more Smart Citations
“…In the context of frauds, high risk perception enables farmers to protect themselves by purchasing only products duly registered by governmental regulators [36]. This result is in line with the study of Ashour et al (2019) [8], who revealed that 80% of the farmers in Uganda had high beliefs about counterfeit herbicides. On the other hand, a comparison of farmers who had purchased fraudulent pesticides and those who had not showed an interesting result.…”
Section: Plos Onesupporting
confidence: 80%
“…Accordingly, they might be more aware of risks of fraudulent pesticides compared to farmers who have not purchased them before. This result is supported by the study of Ashour et al (2019) [8], who reported that farmers who had purchased counterfeit herbicides had a high awareness of their risks and 31% of them had avoided purchasing herbicides in the next year from the same sources because of counterfeiting.…”
Section: Plos Onementioning
confidence: 55%
See 1 more Smart Citation
“…Uganda exhibits similar quality problems for mineral fertilizers (Bold, Kaizzi, Svensson, & Yanagizawa-Drott, 2015) and glyphosate (Ashour, Billings, Gilligan, Hoel, & Karachiwalla, 2016). Moreover, Fairbairn et al (2017) find evidence of degradation in physical quality characteristics of fertilizer (mineral fertilizer that is clumpy, powdery, and discolored); they also find that suppliers with limited credit access and poor storage are also more likely to sell mineral fertilizer of degraded visual quality and compromised content.…”
Section: Limited Capacity Of Agricultural Input Suppliersmentioning
confidence: 87%
“…One particularity of smallholder's pesticide use is their dependence on unauthorized dealers, who often sell products of dubious quality and origin (Ndayambaje et al, 2019;Negatu et al, 2016;Okonya et al, 2019) and with limited knowledge about the products (Yami & van Asten, 2018). Many SSA countries struggle with the problem of illegally sold and/or counterfeit agrochemicals, which may be adulterated or contain banned compounds (Ashour et al, 2019;Okolle et al, 2016). Ashour et al (2019) found that a majority of the herbicides sampled from Ugandan markets contained a different concentration than advertised.…”
Section: The Specific Vulnerabilities Of Smallholdersmentioning
confidence: 99%